Impact of polyploidy on plant tolerance to abiotic and biotic stresses - Tossi, Vanesa E.; Martínez Tosar, Leandro J.; Laino, Leandro E.; Iannicelli, Jesica; Regalado, José Javier; Escandón, Alejandro Salvio; Baroli, Irene; Causin, Humberto Fabio; Pitta-Álvarez, Sandra Irene (Frontiers in Plant Science, 2022)
Polyploidy, defined as the coexistence of three or more complete sets of chromosomes in an organism's cells, is considered as a pivotal moving force in the evolutionary history of vascular plants and has played a major role in the domestication of several crops. In the last decades, improved cultivars of economically important species have been developed artificially by inducing autopolyploidy with chemical agents. Studies on diverse species have shown that the anatomical and physiological changes generated by either natural or artificial polyploidization can increase tolerance to abiotic and biotic stresses as well as disease resistance, which may positively impact on plant growth and net production. The aim of this work is to review the current literature regarding the link between plant ploidy level and tolerance to abiotic and biotic stressors, with an emphasis on the physiological and molecular mechanisms responsible for these effects, as well as their impact on the growth and development of both natural and artificially generated polyploids, during exposure to adverse environmental conditions.